Vaginal microbial diversity of the genital tract of South African adolescent females - Breetzke, Aerin Olivia (Division of Clinical Immunology, 2017)
Young, reproductive-aged women are at highest risk of acquiring human-immunodeficiency virus (HIV). The Women's Initiative in Sexual Health (WISH) study was designed to investigate potential biological reasons for this high risk in HIV negative, South African adolescent females. Little is known about the 'normal' microbiome of this population. As such, the aim of this substudy was to quantify specific bacterial species (L. crispatus, L. jensenii, L. gasseri, L. iners, G. vaginalis and P. bivia) by quantitative real time PCR (qPCR) from adolescent female lateral vaginal wall swabs, and to assess associations between the quantities of these bacteria and bacterial vaginosis (BV) status, inflammation levels, age, hormonal contraceptive usage, and sexually transmitted infections (STIs). Samples were collected from 143 participant adolescent females in total, aged between 16 and 22 years of age, with a median of 18 years of age, from the Masiphumelele Youth Clinic in Cape Town, South Africa. Bacterial DNA was extracted from lateral vaginal wall swabs using the MoBio Powersoil® DNA Isolation Kit after enzymatic digestion. Positive bacterial reference strains were cultured in MRS buffer and Schwedler's broth, after which the DNA was extracted using the Qiagen Blood and Tissue DNA Maxi Extraction Kit. The quality and concentration of the DNA was confirmed using Qubit technology. The positive control DNA was amplified with PCR using species specific primers and the product run on an agarose gel to confirm primer specificity. The positive control DNA was serially diluted from 106 to 10-2 copies/μL to form a standard curve for absolute quantification through qPCR. Multiple steps were taken in order to optimize the qPCR experiments in terms of protocols, initial denaturation and annealing temperatures, cycle length and number, primers, and serial dilutions of the positive control DNA. The optimization for the P. bivia qPCR protocol presented the most issues, with the final quantification results being unreliable and requiring further work. Once the qPCR conditions were optimized for each bacterium; all samples, non-template control and standards were run in triplicate to quantify the number of bacterial copies per ng of DNA for each participant. The average of the three values were used as the final quantities and then used for downstream analyses. The bacterium L. crispatus, L. jensenii and L. gasseri, had median readings of 3.957 copies/ng, 1.568 copies/ng, and 17.58 copies/ng, respectively, with increased L. iners (2807 copies/ng) and G. vaginalis (8540 copies/ng). BV negative participants had increased levels of L. crispatus (p=0.0004, p=0.0002) and L. gasseri (p=0.0016, p<0.0001) in comparison to both BV intermediate and BV positive participants. L. jensenii (p<0.0001) and L. iners (p=0.0461) readings were increased in BV negative participants compared with BV positive and BV intermediate participants, respectively. BV positive participants had increased levels of G. vaginalis in comparison with both BV intermediate (p=0.0059) and BV negative (p<0.0001) adolescents. The 47 immunological factors, assessed via luminex, were categorized into high and low genital inflammation based on the unsupervised analysis by partitioning around medoids (PAM) using an R package 'cluster' with a k-value of 2. The inflammation-low group had increased levels of L. crispatus (p=0.0005), L. gasseri (p=0.033) and L. jensenii (p=0.0046) in comparison to the genital inflammation-high group. In participants with two viral STIs (Herpes Simplex Virus 2 and Human Papilloma Virus), there were increased copies/ng of G. vaginalis in comparison with participants with none (p=0.0098) or one viral STI (p=0.0324). Participants with high-risk HPV subtypes had significantly higher copy numbers of L. crispatus in comparison to the participants with low risk HPV subtypes (p=0.0181). Further, the only association demonstrated between the qPCR-based bacterial levels and the hormonal contraceptive prescribed was indicated by L. jensenii (ANOVA p=0.0222), possibly due to the low copy number readings. In conclusion, BV status, low levels of genital inflammation and the presence of two viral STIs indicate an association with bacterial copy numbers reported in this study, with increased median levels of L. iners and G. vaginalis across all adolescent participants compared to the other reported bacterial copy numbers. This indicates a possible alternate 'normal' microbiota profile of the FGT in adolescents in Masiphumelele.